Statistical analysis of medical data: descriptive statistics and group comparison - Zh. V. Gudinova; L. V. Demakova (Фундаментальная и клиническая медицина)
Here we describe the most common and informative procedures for the primary statistical analysis of medical data. We emphasize the importance of using histogram, normality tests, median, percentiles, confidence intervals, ranking procedures, and as analytical tools. The material is illustrated with step-by-step graphical explanation of applying commercially available software for fulfilling these tasks. The lecture is designed for biomedical students and clinicians.